Upaya Meningkatkan Sikap Toleransi Beragama Peserta Didik Melalui Metode Diskusi di SD Negeri 18 Tangah Koto - Rahmat Irfandi Mz; Nino Andeswari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Education does not only focus on academic achievement, but also plays an important role in shaping the character of students, one of which is tolerance. Tolerance is very much needed in social life, especially in elementary schools that have a diverse student background. This study aims to improve the religious tolerance of fourth-grade students at SD Negeri 18 Tangah Koto through the application of the discussion method. This study used a Classroom Action Research (CAR) approach, which was carried out in two cycles. Each cycle included the stages of planning, implementation, observation, and reflection. The research subjects were 25 fourth-grade students in the 2024/2025 academic year. The results showed an increase in students' tolerance attitudes. In the pre-cycle, only 28% of students achieved mastery, increasing to 60% in cycle I, and finally reaching 80% in cycle II. Thus, the application of the discussion method proved to be effective in increasing students' religious tolerance attitudes.